An ethnographic analysis of selected yoruba proverbs in political media chats: a case study of Governor Olagunsoye Oyinlola (2017)
Language is a powerful tool politicians employ to woo the hearts of electorates and sell their candidature to them. Governor Olagunsoye Oyinlọla, an astute politician and erstwhile governor of Ọṣun State, Nigeria, is one of such politicians who demonstrate their linguistic prowess during their interaction with the masses. Much scholarly attention has been devoted to the analysis of proverbs in Yoruba language in particular as well as in other languages. To the best of the researcher’s knowledge, none of such works focused on the proverbs used by Ex-Governor Olagunsoye Oyinlọla in the programme ‘Open Forum’. This study examines the use of proverbs by Governor Olagunsoye Oyinlọla on a television programme, ‘Open Forum’ aired on Ọṣun State Broadcasting Corporation (OSBC), within the purview of Dell Hyme’s Ethnography of Communication in order to bring to the fore, the aesthetic and persuasive values inherent in proverbs as a means of beautifying language. The data analysed in this study comprised twenty purposively selected proverbs employed by Oyinlọla on the programme. The analysis was based on the appropriateness of the proverbs to their contexts of usage. These proverbs were classified into 4 groups which are: (i) Proverbs that depict some Yoruba beliefs (ii) Proverbs that warn and caution (iii) Proverbs that express power-relationship, and (iv) Proverbs associated with self-evaluation. The first group of proverbs was used to justify some of the activities of his administration while in government and to pledge his commitment to improving the lots of the people he was governing. The second group was used to warn those who were vandalising government’s infrastructure and the opposition party. The third group of proverbs was used to express disappointment at the attitude of the opposition party, respect and veneration for the retired military officers and the traditional rulers who were precursors of modern democracy. He used the fourth group of proverbs to assess his performance in office. Linguistic skills entail more than the mastery of a linguistic code that allows the language user to produce sentences that are grammatical, they also involve knowing how to use language, spiced with proverbs and idiomatic expressions, in different social settings